Prenatal Phenotype in Nonimmune Hydrops Fetalis [A160]. (May 2022) - Makhamreh, Mona M.; Rice, Stephanie; Critchlow, Elizabeth; Araji, Sarah; Berger, Seth; Al-Kouatly, Huda B.
Abstract : INTRODUCTION: Nonimmune hydrops fetalis (NIHF) is defined by fluid accumulation in ≥2 fetal compartments without alloimmunization. Structural anomalies on prenatal imaging should be assessed for genetic diagnosis. Our goal was to describe the prenatal phenotype of a NIHF cohort based on prenatal imaging, also determine the significance of prenatal imaging in the genetic workup. METHODS: The Hydrops-Yielding Diagnostic Results of Prenatal Sequencing (HYDROPS) study is an ongoing prospective series of NIHF with negative standard workup. Trio exome sequencing (ES) was performed and prenatal records were reviewed. The primary outcome was identifying major organ system abnormalities in NIHF. The secondary outcome was comparing major organ system abnormalities in NIHF in cases diagnosed or possibly diagnosed by ES to cases that remained undiagnosed. RESULTS: In 30 cases, major organ system abnormalities were: musculoskeletal (MSK) 9 (30%); central nervous system (CNS) 7 (23%); cardiac 6 (20%); and renal 2 (6.7%). Among 16 cases with major organ system abnormality on prenatal imaging, 15 (93.7%) were diagnosed or possibly diagnosed by ES, while 1 (6.3%) was undiagnosed. Of 14 cases with no major organ abnormalities, 6 (42.9%) were diagnosed or possibly diagnosed by ES while 8 (57.1%) were undiagnosed. The presence of major organ abnormalities in NIHF increased the diagnostic yield of ES. ( P =.004). CONCLUSION: The most common major organ system abnormalities on prenatal imaging in NIHF were MSK, CNS and cardiac. Most NIHF cases with congenital abnormalities on prenatal imaging yielded a diagnostic or possibly diagnostic result on ES. Comprehensive prenatal phenotyping increases the diagnostic yield in NIHF.